Endothelial Cell-Derived TGF-β Promotes Epithelial-Mesenchymal Transition via CD133 in HBx-Infected Hepatoma Cells - Rawal, Preety; Siddiqui, Hamda; Hassan, Mohsin; Choudhary, Manish Chandra; Tripathi, Dinesh M.; Nain, Vikrant; Trehanpati, Nirupama; Kaur, Savneet (Frontiers in Oncology, 2019)
Background: Hepatitis B-X Protein (HBx) encoded in Hepatitis B virus (HBV) is known to play a critical role in development and progression of HBV induced hepatocellular carcinoma (HCC). HBx interacts with and activates various cells in HCC microenvironment to promote tumor initiation, progression and invasion. In this study, we investigated how surrounding stromal cells interact with HBx-infected hepatoma cells by a series of in vitro co-culture studies. Methods: Huh7 hepatoma cells were cultured and transfected with the mammalian expression vector pGFP-HBx. Co-culture assays were performed between HBx-transfected Huh7 cells and conditioned media (CM) from stromal cells [endothelial cell lines (HUVECs) and hepatic stellate cell lines (LX2 cells)]. The effect of these interactions was studied by a series of functional assays like chemotaxis, invasion, and wound healing scratch assays. Also, quantitative real time (RT)-PCRs of the mesenchymal genes was performed in the hepatoma cells with and without the co-cultures. Hep3B cells with an integrated HBV genome were taken as positive controls. Results: HBx-transfected Huh7 cells cultured in presence of CM from HUVECs illustrated enhanced migration and tube formation as compared to HBx-transfected cells cultured alone or co-cultured with LX2 cells. HBx-transfected hepatoma cells incubated with CM from HUVECs also expressed mesenchymal genes including Thy1, CDH2, TGFβR1, VIM, and CD133. ELISAs revealed increased levels of TGF-β in CM from HUVECs. In comparison to unstimulated HBx-transfected Huh7 cells, TGF-β stimulated cells displayed increased invasive properties and mesenchymal gene expression. RT-PCR and flow cytometry analysis further demonstrated that incubation with either CM from HUVECs or TGF-β significantly increased the expression of a stemness marker, CD133 in HBx-infected hepatoma cells. Gene inhibition experiments with CD133 siRNA showed a downregulation of mesenchymal gene expression and properties in TGF-β induced HBx-infected hepatoma cells as compared to that observed in control siRNA treated cells, indicating CD133 as one of the key molecules affecting epithelial to mesenchymal transition (EMT) in HBx-infected cells. Conclusion: The study indicates that secretory factors like TGF-β from neighboring endothelial cells may enhance expression of CD133 and impart an aggressive EMT phenotype to HBx-infected hepatoma cells in HBV induced HCC.